Hydrological characterization and social dynamics of polders in the Bengal Delta [Abstract only] - Jampani, Mahesh; Matheswaran, Karthikeyan (2023)
Polders in the floodplains of the Ganges-Brahmaputra delta in Bangladesh play a critical role in supporting intensive agricultural production and the livelihoods of around eight million people. Polderization is promoted to reduce environmental vulnerabilities against flood inundation, coastal erosion, and salinity intrusion. These land areas are low-lying islands consisting mainly of alluvial sediment deposits, and almost half (~1.2 million ha) of the coastal zone in the region is polderized. Agriculture is the primary reason for the polderization of the region, where paddy rice is the major irrigated crop. Around 139 polders in Bangladesh spread across the Gangetic-Brahmaputra delta region, and they altered the delicate balance between human activity and the floodplains' natural hydrological process, resulting in numerous evolving problems. These include the geomorphological evolution of the river channels and flood plains, water logging and drainage congestion within the polder system, sea-level rise, tidal surges, and salinity intrusion. Coastal and inland salinity is a significant problem in these polders, often influencing crop yields and further agricultural productivity and freshwater availability. We explicitly look at two polders to evaluate the distinct socio-hydrological characteristics of these systems. We used several secondary data sources and literature (grey and scientific) to evaluate the hydrological characteristics, groundwater heterogeneity and social dynamics to understand and evaluate the underlying mechanisms and intrinsic links between systems that influence water balance, saline water intrusion, and crop production. The initial results highlight the complex dynamics of the polder system, often influenced by water availability, irrigated water use, seasonality, and, above all, stakeholders' perceptions. Overall, this work provides an improved understanding of the biophysical dynamics and social linkages and sets the basis for implementing a larger detailed socio-hydrological framework.